Protein, Oil and Fatty Acid Contents of Hybrids and Their Parents of Sunflower (Helianthus annuus L.) - OZ, MEHMET; KARASU, ABDULLAH; CAKMAK, IBRAHIM; TANJU GOKSOY, A.; OZMEN, NESE (Asian Journal of Chemistry, 2010)
This research was carried out to determine the contents of protein, oil, fatty acids and the correlation coefficients and heterosis effects for sunflower parents and hybrids. Field trials were conducted during 2004- 06, using randomized complete block design with four replications in Mustafa Kemal Pasa, Bursa, Turkey. Three cytoplasmic male sterile lines (CMS01, CMS10 and CMS23) and 2 restorer lines (RHA03 and RHA10) were crossed and obtained 6 hybrid lines (CMS01 × RHA03, CMS10 × RHA03, CMS23 × RHA03, CMS01 × RHA10, CMS10 × RHA10 and CMS23 × RHA10). Protein contents varied among 15.92- 23.59 %, oil contents 36.33-50.15 %, oleic acid rates 27.91-49.71 %, linoleic acid 43.25-60.38 %, palmitic acid 3.32-6.70 % and stearic acid rates 3.30-6.48 %. Heterosis rates were found -2.6 to +27.07 % for protein content, -9.62 to +19.88 % for oil, -10.54 to +30.88 % for oleic acid, -24.81 to +5.20 % for linoleic acid, -41.92 to +16.11 % for palmitic acid and -4.62 to +69.81 % for stearic acid rates. Protein content was negatively correlated with oil (r = -0.468**), linoleic acid (r = -0.495**) and palmitic acid (r = -0.349*) and positively correlated with oleic acid (r = 0.482**) and stearic acid (r = 0.544**). It was recorded that there was negative and the highest correlation coefficient between oleic acid and linoleic acid (r = -0.958**), whereas the high positive correlation was fixed between oleic acid and stearic acid (r = 0.576**).